Segmental intestinal reconfiguration (SIR) for lengthening and tapering of dilated short bowel: Technique and case report - Vasily V. Nikolaev; Julia Averyanova (Elsevier, 2023)
Introduction: Some patients presenting with dilated short bowel suffer from dysmotility, leading to stasis and consequent bacterial overgrowth. These patients are candidates for intestinal reconfiguration surgery. We suggest a technique of lengthening and tapering of the dilated short bowel segment named segmental intestinal reconfiguration (SIR) based on the modified Yang-Monti principle and submit the first clinical experience. Case presentation: The SIR technique was applied in a 10 years old patient with segmental bowel dilation of ultra-short bowel due to intestinal atresia and resection, who received parenteral nutrition 50% of the daily requirements. He was diagnosed with liver disease associated with intestinal failure, metabolic bone disorder, and polyarthritis. The dilated bowel loop was transected in three places to produce two segments 6 cm long. Antimesenteric borders of the segments were incised along, resulting in 2 rectangular flaps 12x6 cm. The flaps were closed into a tube diagonally to form two neosegments, sutured together and with the open intestinal ends. The length of the reconfigured bowel loop after SIR increased from 12 to 26 cm. The signs of dysmotility disappeared 3 weeks after the operation. In 18 months, the mid-term outcome was evaluated. There were no bacterial overgrowth or dysmotility episodes during this period. The child has become active, gaining weight and height. Parenteral nutrition was reduced in half. Conclusion: First clinical application of the SIR technique showed its simplicity, feasibility and positive effect on the motility.